Effect of topdressing with nitrogen and boron on the yield and quality of rapeseed - Ladislav Varga; Otto Ložek; Ladislav Ducsay; Peter Kováčik; Tomáš Lošák; Jaroslav Hlušek (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2010)
Field trials with winter rape (Brassica napus L. var. napus) variety Rasmus were established in August in the years 2002–2004 at the experimental station in Kolíňany which belongs to the Slovak University of Agriculture in Nitra. In the experiments we explore the effect of supplementary spring topdressing of rape with nitrogen and boron in the BBCH 29–30 stage with regard to the yields of seeds and their qualitative parameters (TSW, content of oil and crude protein). In the experiment we applied DAM–390 (solution of ammonium nitrate and urea, 30% N) at a rate of 30 kg N/ha and Humix Bór (humic acids + N, K, B) at a rate of 0.240 kg B / ha. The different climate conditions in the respective years had a significant effect on yields of rapeseed and ranged as follows: 2003: 1.80–2.29 t / ha; 2004: 2.60–3.35 t / ha; 2005: 2.45–3.29 t / ha. The significant decrease in seed yields in the first year of the experiment was caused namely by the deficit in precipitation in January, February and June 2003 and high temperatures in May and June in the same year. In terms of the individual years and the three-year average the application of Humix Bór itself did not significantly improve the yield and qualitative parameters of seeds compared to the unfertilised control. In a three-year average the application of the N fertiliser alone or in combination with Humix Bór increased seed yields and the crude protein content by 22.4–30.7 % and 4.0–4.9 rel. %, respectively, compared to the unfertilised control. The significantly highest seed yields (2.98 t / ha) were achieved when the plants were treated with a combination of nitrogen and Humix Bór as compared to all the other treatments (2.28–2.79 t / ha). The oil content in seeds increased significantly to 44.1% only when treated with a combined application of DAM–390 and Humix Bór as against the unfertilised control (42.8%). Fertilisation did not change the TSW which ranged only between 4.47 and 4.67 g.